STUDI TENTANG PERBANDINGAN PENDIDIKAN JASMANI ANTARA INDONESIA DENGAN JEPANG - Juliantine, Tite (Jurnal Pendidikan Jasmani Indonesia, 2006)
Physical education is an educational process through physical activities to achieve the goalof education, so that by means of teaching process it is hoped that the change of pupil’sbehavior will be occurred. In a framework of children education as a totality, it must cover upthe unity between physical and spiritual aspects. There are no subject of lesson with ascompound and complete goal as physical education. Unfortunately, this goal hasn’t entirelyachieved yet because its realization isn’t in accordance with it hopes. There are manyproblems occurred such as the limitedness of its means and infrastructure, the number andquality of teachers which is insufficient, etc. until now, such constraints are not overcome.Therefore, writer is attracted to examine the compurgation of physical education betweenIndonesia and Japan. Why Japan ? Because Japan has become the most advanced countryin Asia and it has had such particular tricks in its efforts to arrange a more effectivelylearning process, so that it is hoped that Indonesia could adopt positive things that could beproperly applied in Indonesian situation and condition, so that the goal of physical educationcould be achieved optimally.Keywords : Physical Education, Physical Education in Indonesia, Physical Education inJapan.